Aircraft Maintenance- New Trends in General Aviation - Bugaj, Martin (Promet - Traffic&Transportation, 2005)
Maintenance organizations assist in ensuring that all aeronauticalproducts built, operated or maintained under controlconform to national and international ailworthiness standards.Ensuring that these standards are met involves a vastnetwork of organizations and personnel in general aviation.Standards and Procedures is responsible for the coordinationand management of all regional maintenance and manufacturingactivities, other than those related to Licensing andTraining. This includes acting as a central coordination andcommunication point for other Civil Aviation.